0275 Effect of acutely induced severe OSA on AD plasma biomarkers. (25th May 2022) - Kam, Korey; Jun, Jonathan; Bubu, Omonigho; Mullins, Anna; Parekh, Ankit; Gu, Chenjuan; Pham, Luu; Rapoport, David; Ayappa, Indu; Osorio, Ricardo; Varga, Andrew
Abstract: Introduction: Obstructive sleep apnea (OSA) has been associated with Alzheimer's disease (AD) progression but a causal relationship is unclear. We hypothesized that OSA can influence (AD) biomarkers including beta-amyloid (Aβ) and tau, as well as neural filament light chain (NfL). Methods: To test this hypothesis, we examined plasma tau, NfL, Aβ42, and Aβ40 in a randomized crossover study of OSA vs. 3-night CPAP withdrawal in 30 subjects with severe OSA adherent to CPAP. We compared the overnight change in evening to morning plasma samples across the untreated night (off) versus CPAP treated night (on). Paired t-tests were used to compare measures across sleep conditions while hierarchical linear regression with difference in the overnight change of each biomarker between conditions were set as dependent variables with age and sex as covariates. Results: Of the 30 subjects, mean age was 52 years and 27% were women. As expected, CPAP withdrawal caused sleep disruption and recurrence of underlying OSA. Sleep architecture measures including %N3 (Off: 6.1% [3.7-8.5], On: 15.1% [10.6-19.6], p<0.001), %REM (Off: 11.8% [8.8-14.7], On: 20.6% [18.3-22.9], p<0.001), and measures of breathing such as AHI4% (Off: 63/hr [54-72], On: 3/hr [2-4], p<0.001), SpO2 below 90% (Off: 20 min [14-26], On: 1 min [0-3], p<0.001), and SpO2 min (Off: 77% [74-80], On: 88% [86-90], p<0.001) were all significantly different in the untreated versus CPAP treated nights. Compared to CPAP treatment, the overnight change in NfL was increased relative to CPAP withdrawal while the overnight change in Aβ40 was decreased relative to CPAP withdrawal. No change was observed with tau or Aβ42. We found that difference in %N3 between the on- and off-CPAP conditions significantly explained an additional 15.7% of the variance beyond a base model including age and sex alone. No other difference in sleep architecture or apnea severity/hypoxemic burden metric significantly contributed to the variance in overnight change in Aβ40 between conditions, and we identified no significant predictors for variance in overnight change in NfL. Conclusion: This study presents some of the first evidence for an effect of acute CPAP withdrawal on neurodegenerative and amyloid plasma biomarkers and implicates a role for N3 sleep in this effect. Support (If Any): AASMF Focus award, NIDDK P30DK072488, R01AG066870, K24HL109156